Pengetahuan Keamanan Pangan Mahasiswa Mengenai Lima Kunci Keamanan Pangan Keluarga - Tenggana, Marcellinus Elwan; Rahayu, Winiati P.; Wulandari, Ratna (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2020)
Development of the Five Keys for Family Food Safety module for food safety cadres needs to be done to facilitate cadres in understanding the material provided. This study aims to analyze the food safety knowledge of college students and evaluate the Five Keys for Family Food Safety teaching materials developed by the Badan POM. The respondents of the survey were college student of IPB University. The results of the evaluation of food safety knowledge of college students after being educated using the Five Keys for Family Food Safety module showed an increasing in the value of knowledge by 16%. The initial value of college student knowledge was 71 and increased became 87%. Non-parametric test results indicate that there were significant differences between the two values ​​with the Sig. 2 tailed at 0.000. The evaluation results of the Five Keys for Family Food Safety module show very good criteria with an average value of 81%. The values for display, material content and benefit were 81, 82, and 78%. This indicate that Five Keys for Family Food Safety module is ready to be used as teaching material for food safety.